Lipomyelomeningocele—Controversies in Management - Abhishek Singh; Samarendranath Ghosh; Anup Kr. Chaudhuri; Shahid Iftekhar Sadique; Subhamitra Chaudhuri (Indian Journal of Neurosurgery)
Management of lipomyelomeningocele is one of the most discussed and controversial topics in recent years. Till date, there is no consensus on the most appropriate mode of management for lipomyelomeningocele, particularly in asymptomatic patients. This article tries to sort out controversies associated with lipomyelomeningocele based on various literatures and also takes into account patient profile of a developing country.